Next Step in Gene Delivery: Modern Approaches and Further Perspectives of AAV Tropism Modification - Maxim A. Korneyenkov; Andrey A. Zamyatnin (MDPI AG, 2021)
Today, adeno-associated virus (AAV) is an extremely popular choice for gene therapy delivery. The safety profile and simplicity of the genome organization are the decisive advantages which allow us to claim that AAV is currently among the most promising vectors. Several drugs based on AAV have been approved in the USA and Europe, but AAV serotypes' unspecific tissue tropism is still a serious limitation. In recent decades, several techniques have been developed to overcome this barrier, such as the rational design, directed evolution and chemical conjugation of targeting molecules with a capsid. Today, all of the abovementioned approaches confer the possibility to produce AAV capsids with tailored tropism, but recent data indicate that a better understanding of AAV biology and the growth of structural data may theoretically constitute a rational approach to most effectively produce highly selective and targeted AAV capsids. However, while we are still far from this goal, other approaches are still in play, despite their drawbacks and limitations.